2009
DOI: 10.1182/blood-2008-12-195073
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ–triggered indoleamine 2,3-dioxygenase competence in human monocyte-derived dendritic cells induces regulatory activity in allogeneic T cells

Abstract: The role of the tryptophan-metabolizing enzyme indoleamine 2,3-dioxygenase (IDO) in down-regulating human alloresponses has recently been controversially debated. We here demonstrate that human monocyte-derived dendritic cells (mDCs) can be endowed with sustained IDO competence in vitro by 48-hour activation with lipopolysaccharide (LPS) and interferon-gamma (IFN-␥). IFN-␥ also amplified proinflammatory cytokine secretion during activation. Yet, on reculture after activation cytokine production ceased, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
163
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 156 publications
(179 citation statements)
references
References 48 publications
13
163
1
2
Order By: Relevance
“…This phenomenon is quite unusual [16], since IDO is often regarded as a feedback mechanism to inflammation, which may be indicated by proinflammatory cytokines [6,8]. However, this finding corroborates our concept that proinflammatory DC cytokine production and IDO induction are separate processes [6].…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…This phenomenon is quite unusual [16], since IDO is often regarded as a feedback mechanism to inflammation, which may be indicated by proinflammatory cytokines [6,8]. However, this finding corroborates our concept that proinflammatory DC cytokine production and IDO induction are separate processes [6].…”
Section: Discussionsupporting
confidence: 86%
“…In our recent studies, we observed that strong IDO induction as a counterregulatory mechanism mediated APC activation [6,15], particularly when DCs were polarized by IFN-γ toward a DC1 phenotype [30,31]. Here, consistent with previous literature [25,26], we found that the cytokine and PGE 2 -matured DCs failed to produce the key cytokines characterizing a DC1 phenotype IL12p70 and IFN-γ [30,32] (Fig.…”
Section: Pge2 Stimulates DC Ido Competence But Not Proinflammatory Cysupporting
confidence: 90%
See 3 more Smart Citations